The The Influence of Problem Based Learning Models and Audio Visual Learning Media on Economic Learning Outcomes - Febriyani, Farah; Anisah, Aan; Rusdiyana, Rusdiyana (Annpublisher, 2025)
Background. Problem-based Learning is an innovative learning model that begins by providing contextual problems to stimulate students to learn and find solutions, enabling them to think critically when solving problems. Problem-based Learning encourages students to find problem-solving strategies that can help improve their abilities. Aims. Describe and prove the influence of the Problem-Based Learning model and audio-visual learning media on economic learning outcomes in grade XI students of Academic MAN 2 Banyumas. Method. The type of research employed is quantitative, with an experimental approach. The statistical tests used include validity tests, reliability tests, hypothesis tests, normality tests, Wilcoxon tests, homogeneity tests, Mann-Whitney tests, and normality gain tests. Result. There is an influence of the problem-based learning model and audiovisual media on learning outcomes. The hypothesis accepted by HI is that Problem-Based Learning has a positive effect on students' economic learning outcomes. H2: Audio-visual media have a positive effect on students' economic learning outcomes. Conclusion. There is a significant difference between the learning outcomes of students who use the Problem Based Learning Model and Audio Visual Media and the learning outcomes of students who do not use the Problem Based Learning and Audio Visual Media Learning Model in class XI Academic MAN 2 Banyumas Implementation. Educators utilize the Problem-Based Learning Model and Audiovisual Media to make learning enjoyable, ensuring that students are engaged and not bored when learning economics subjects.